Pedagogical Translation for Vocabulary Learning: The Parallel-Text Approach - Lo, Siowai (Taiwan Journal of TESOL, 2023)
This study takes a fresh look at vocabulary learning from the lens of professional translation practice and proposes integrating parallel texts with translation tasks to foster vocabulary learning. The study adopts a quasiexperimental design to examine the effectiveness of using parallel texts in pedagogical translation to foster EFL learners' lexical gains and vocabulary retention. It compares learners' foreign language vocabulary gains as a direct result of pedagogical translation tasks completed under two conditions: (1) Translation tasks with parallel texts (the "parallel-text approach") versus (2) translation tasks without parallel texts. A total of 40 Chinese EFL sophomores in social sciences participated in this study. The study consists of two experiments with identical procedures to allow all participants to swap roles and experience vocabulary learning under both conditions. Qualitative and quantitative data were retrieved from learners' drafts, revisions, and post-tests. The potential benefits of using parallel texts in pedagogical translation tasks were revealed in both between-group and within-subjects analyses. Empirical evidence of the pedagogical value of parallel texts may help language educators to innovate and facilitate learners to rethink their strategies.